Pharmacotherapy in Psychiatric Disorders of Children: Current Evidence and Trends - Kölch, M.; Plener, P. L. (Pharmacopsychiatry, 2016)
Pharmacotherapeutic interventions are available for most psychiatric disorders in children. Evidence for these interventions varies, depending on the targeted disorders. For attention-deficit/hyperactivity disorder, a sound database on efficacy and safety of medication exists. For other common disorders or psychopathological phenomena like disruptive behavior, anxiety disorders, depressive disorders, or autism, data on efficacy and safety are much scarcer. This selective review aims to provide an overview about current psychopharmacological interventions in child and adolescent psychiatry. The literature indicates either a lower efficacy than other interventions or less beneficial effects compared to possible adverse events in these cases. Most guidelines recommend psychopharmacotherapy in children to be embedded in a psychosocial or therapeutic intervention plan. Decision for medication depends on the severity of symptoms, chronicity, and, most important, impairment of the child in academic performance, family relationships, and everyday life. The high rates of off-label use in the age group of children are often due to a lack of market authorization studies less indicative of low efficacy. As adverse events need to be monitored closely, pharmacotherapy should mainly be restricted to experienced mental health care providers.
Keywords: children; psychopharmacotherapy; ADHD; internalizing disorders; safety